DIGITAL MARKETING STRATEGIES TO INCREASE BRAND AWARENESS OF KOPI JANJI JIWA AMONG GEN Z IN JAKARTA - Fedianty Augustinah; Ferdi Angga Kusuma; Liling Listyawati (Yayasan Nuraini Ibrahim Mandiri, 2026)
Amidst the rise of digital fatigue among Generation Z, maintaining brand awareness is a critical challenge for today's coffee shop businesses. This explanatory research using quantitative methods explores the contribution of digital marketing strategies to brand awareness (Y) of Kopi Janji Jiwa in South Jakarta. The four marketing pillars examined include content marketing (X_1), influencer marketing (X_2), social media advertising (X_3), and engagement & community building (X_4). Primary data were collected from 398 local respondents through a structured questionnaire with a Likert scale (1–5) using a non-probability purposive sampling method. Multiple linear regression, F-test, t-test, and R^2 confirmed that all digital pillars collaborate significantly in shaping brand awareness (F_count = 243.7; p = 0.000). This statistical model recorded a coefficient of determination (R2) of 0.714, indicating that 71.4% of brand awareness dynamics are determined by the implemented digital strategy, while the remaining 28.6% is driven by external factors outside the test variables. Partially, each variable was positive and significant (p<0.05). Collaboration with influencers emerged as the primary driver (β=0.341; t=8.12), followed by content marketing (β=0.287; t=6.83), community building (β=0.253; t=5.94), and social media advertising (β=0.198; t=4.57). Based on these baseline findings, it is recommended that brand policy stakeholders focus funding allocation on partnerships with micro-influencers and interactive promotional materials to address audience fatigue with conventional advertising.